1995
DOI: 10.1209/0295-5075/32/2/014
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in the Infinite- U Hubbard Model

Abstract: PACS. 75.10-b -General theory and models of magnetic ordering. PACS. 71.27 + a -Strongly correlated electron systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 20 publications
(20 reference statements)
2
47
1
Order By: Relevance
“…As mentioned above, the fully polarized ferromagnetic state is the ground state for the open-boundary t-t ′ Hubbard model 4,5 . This is also the case with the open-boundary Hubbard ladders 14,15 . Then, in the thermodynamic limit, the spiral ground state (in PBC) can either give way to the ferromagnetic state, remain the ground state, or become degenerate with the ferromagnetic one.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…As mentioned above, the fully polarized ferromagnetic state is the ground state for the open-boundary t-t ′ Hubbard model 4,5 . This is also the case with the open-boundary Hubbard ladders 14,15 . Then, in the thermodynamic limit, the spiral ground state (in PBC) can either give way to the ferromagnetic state, remain the ground state, or become degenerate with the ferromagnetic one.…”
mentioning
confidence: 72%
“…Ferromagnetic behavior is also found in the ladders where U is infinite 14,15 , so it is intriguing to study whether a spiral state appears in this system as well, and if so, whether A(k, ω) exhibits a DW-like behavior. The Hamiltonian is given by…”
mentioning
confidence: 99%
“…In practice, this leads to a large entanglement between the system and environment blocks and therefore a slower fall-off of the eigenvalues of the density matrix, requiring many more states to be kept to attain a given accuracy. This scaling of the required number of states has been studied systematically for the case of two-dimensional noninteracting spinless fermions, where it is found that the number scales exponentially with the linear dimension of the lattice [90,95]. It is not completely clear that this exponential scaling is fundamental for system block environment block all systems; in fact, noninteracting particles are probably the worst case because of the absence of length scales in the wave functions and because of the highly degenerate gapless excitation spectrum.…”
Section: Real-space Algorithm In Two Dimensionsmentioning
confidence: 99%
“…It is well known that the ferromagnetic Nagaoka [16] state is stabilized when one electron is added to the half filled system. Different works [18][19][20] indicate that a partially polarized FM state is favored for a finite range of concentrations away from half filling. In addition, we have recently found numerical evidence of itinerant ferromagnetism in the PAM for the mixed valence regime and |V | < ∼ |t| [5,6].…”
Section: B) Virtual States Lowest Energymentioning
confidence: 99%